2007
DOI: 10.5897/ajb2007.000-2437
|View full text |Cite
|
Sign up to set email alerts
|

Biological approach to oil spills remediation in the soil

Abstract: Perhaps there is no any other raw material that has impacted so much, and found wide application on human civilization than petroleum hydrocarbon (PHC). The paradox is that it is this same black gold that threatens human environment. PHC pollution in the environment, as well as the importance of natural interactions amongst living entities to arrest the problems hitherto caused by oil spills are hereby examined. Biological approaches to pollution remediation, which include phytoremediation, bioremediation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 16 publications
1
16
0
10
Order By: Relevance
“…[3], that the impact of hydrocarbon on the acidity of soil as it prevents leaching of basic salts as well as leads to production of organic acids. There was a distinct increase in soil pH when samples were taken five days after contamination, [9] had previously reported that such variability in soil pH which could arise during organic decay processes which may result in the formation of both acid and base forming chemicals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3], that the impact of hydrocarbon on the acidity of soil as it prevents leaching of basic salts as well as leads to production of organic acids. There was a distinct increase in soil pH when samples were taken five days after contamination, [9] had previously reported that such variability in soil pH which could arise during organic decay processes which may result in the formation of both acid and base forming chemicals.…”
Section: Resultsmentioning
confidence: 99%
“…A hot dilute potassium hydroxide (KOH) was used to produce an activated carbon such that the solid to liquid ratio is 1:10 in g/cm 3 . The mixture was then left overnight at room temperature in a conical flask.…”
Section: Raw Materials Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Yakubu (2007), o termo biorremediação pode ser definido como um processo biotecnológico no qual se utiliza o metabolismo de micro-organismos para a eliminação rápida de poluentes, com o objetivo de reduzir sua concentração a níveis aceitáveis, transformado-os em compostos de baixa toxicidade.…”
Section: Biodegradação De Poluentes E Biorremediação De áReas Impactaunclassified
“…Hydrocarbon degradative process is widely distributed among numerous genera or taxa [14] and biodegradation of hydrocarbons using microorganisms has been established as an efficient, economic and versatile approach [15][16][17][18][19]. Microorganisms degrade hydrocarbon contaminants and utilize the resulting compounds as nutrients and energy sources for growth and reproduction [20] and are depending on the chemical nature of the compounds and on environmental determinants [21].…”
Section: Introductionmentioning
confidence: 99%